Farmers and Markets in Tanzania how policy reforms affect rural livelihoods in Africa - Ponte, Stefano (Dar es Salaam Mkuki na Nyota, 2002)
The role of African agriculture in global markets and the role of agriculture in national economies have changed profoundly in the last twenty years. Economic reforms have forced the withdrawal of the state from agricultural markets. Livelihoods have become increasingly commercialized. Rural households are restructuring the ways they manage their economic activities and transforming their social relations. This book is about the contradictions of liberalization and the complexity of farmers' responses to the changing role of states and markets. Its theoretical and empirical material will interest policy-makers, development practitioners and scholars of development studies, political economy, economics, political science, and sociology
Includes bibliographical references and index.
Keywords: Agriculture and State, Agricultural Economic aspects Agriculture Economic Productivity Rural Development